Loss of N-Glycanase 1 Alters Transcriptional and Translational Regulation in K562 Cell Lines. Issue 5 (1st May 2020) - Mueller, William F; Jakob, Petra; Sun, Han; Clauder-Münster, Sandra; Ghidelli-Disse, Sonja; Ordonez, Diana; Boesche, Markus; Bantscheff, Marcus; Collier, Paul; Haase, Bettina; Benes, Vladimir; Paulsen, Malte; et al.
Abstract: N-Glycanase 1 (NGLY1) deficiency is an ultra-rare, complex and devastating neuromuscular disease. Patients display multi-organ symptoms including developmental delays, movement disorders, seizures, constipation and lack of tear production. NGLY1 is a deglycosylating protein involved in the degradation of misfolded proteins retrotranslocated from the endoplasmic reticulum (ER). NGLY1-deficient cells have been reported to exhibit decreased deglycosylation activity and an increased sensitivity to proteasome inhibitors. We show that the loss of NGLY1 causes substantial changes in the RNA and protein landscape of K562 cells and results in downregulation of proteasomal subunits, consistent with its processing of the transcription factor NFE2L1. We employed the CMap database to predict compounds that can modulate NGLY1 activity. Utilizing our robust K562 screening system, we demonstrate that the compound NVP-BEZ235 (Dactosilib) promotes degradation of NGLY1-dependent substrates, concurrent with increased autophagic flux, suggesting that stimulating autophagy may assist in clearing aberrant substrates during NGLY1 deficiency.